Acoustic Emission Monitoring of Metals - McCrory, John P.; Vinogradov, Aleksey; Pearson, Matthew R.; Pullin, Rhys; Holford, Karen M. (Acoustic Emission Testing, 2022)
This chapter introduces readers to the particularities associated with AE monitoring of metals and metallic structures through several example studies. The chapter begins with an overview of the failure mechanisms of metals, and a demonstration of AE’s potential as a diagnostic tool for understanding the evolution of dislocation structures during plastic deformation, up to the critical stage of crack initiation. The propagation of AE in metallic plate-like structures is then described alongside a study exemplifying the empirical determination of the dispersive properties of the primary Lamb wave modes in a 2 mm thick steel plate. As fatigue cracking is one of the most prominent causes of failure of metallic structures, three example studies are then described which highlight the ability of AE to detect, locate, and characterise cracking and crack growth. The first of these is a location study in which AE sources in a complex-geometry aluminium specimen subject to cyclic loading were located to within 3.42–20.2 mm of the cracking location, depending on the location method used. Two examples of AE characterisation approaches for identifying signals from fatigue cracking are then described; the first of which implements a principal component analysis of hit data collected from an aircraft landing gear component; and the second of which analyses the spectral information of wavestream recordings from a steel beam specimen. This chapter should educate the reader on a wide range of approaches to AE in metals, and further reading and examples can be found in the references contained throughout.